Acetylation and Deacetylation of DNA Repair Proteins in Cancers - Li, Shiqin; Shi, Bingbing; Liu, Xinli; An, Han-Xiang (Frontiers in Oncology, 2020)
Hundreds of DNA repair proteins coordinate together to remove the diverse damages for ensuring the genomic integrity and stability. The repair system is an extensive network mainly encompassing cell cycle arrest, chromatin remodeling, various repair pathways, and new DNA fragment synthesis. Acetylation on DNA repair proteins is a dynamic epigenetic modification orchestrated by lysine acetyltransferases (HATs) and lysine deacetylases (HDACs), which dramatically affects the protein functions through multiple mechanisms, such as regulation of DNA binding ability, protein activity, post-translational modification (PTM) crosstalk, and protein–protein interaction. Accumulating evidence has indicated that the aberrant acetylation of DNA repair proteins contributes to the dysfunction of DNA repair ability, the pathogenesis and progress of cancer, as well as the chemosensitivity of cancer cells. In the present scenario, targeting epigenetic therapy is being considered as a promising method at par with the conventional cancer therapeutic strategies. This present article provides an overview of the recent progress in the functions and mechanisms of acetylation on DNA repair proteins involved in five major repair pathways, which warrants the possibility of regulating acetylation on repair proteins as a therapeutic target in cancers.